Characterization of physicalquality and flavour profile of Arabica coffee bean of Maragogype variety (Coffea arabica L. var. Maragogype Hort. Ex Froehner) and mother plant selection in East Java - Dwi Nugroho; Surip Mawardi; Yusianto Yusianto; Rins Arimar Setyowati (Indonesian Coffee and Cocoa Research Institute, 2012)
Development of specialty coffee product needs to be done by producing a product that has a good flavor, unique, and different from the axisting specialty coffee products. One of the varieties of Arabica coffee that has good potential to be developed into a specialty coffee is Maragogype coffee. This paper discusses the results of selection and characterization of physical and flavor quality of Arabica coffee varieties Maragogype in East Java. Selection was done in PTPN XII at Pancur/Angkrek and Kayumas Estate. It was obtained two superior genotypes those have high productivity and good taste, they are MP3 and MP4 with of productivity of 7,985.3 and 5,985.3 g cherries/tree, respectively. Maragogipe varieties showed good physical quality, in which 99% of bean belong to the large been category, whiches the highest of 1,000 beens, and good bulk density and apparent swelling. MP3 genotype had a floral, citrus acidity, mild, and very good sweetness characteristics. MP mix had the showed same characteristics, but its intensity was not as high as MP3. MP4 has herbal and flora characteristics with bitter after taste.Key words : Coffea arabica, maragogype, specialty coffee, characterization, selection, flavor, variety.